Comparison of high throughput RNA sequences between Babesia bigemina and Babesia bovis revealed consistent differential gene expression that is required for the Babesia life cycle in the vertebrate and invertebrate hosts - Capelli-Peixoto, Janaina; Saelao, Perot; Johnson, Wendell C.; Kappmeyer, Lowell; Reif, Kathryn E.; Masterson, Hayley E.; Taus, Naomi S.; Suarez, Carlos E.; Brayton, Kelly A.; Ueti, Massaro W. (Frontiers in Cellular and Infection Microbiology, 2022)
Bovine babesiosis caused by Babesia bigemina and Babesia bovis is an economically important disease that affects cattle worldwide. Both B. bigemina and B. bovis are transovarially transmitted by Rhipicephalus ticks. However, little is known regarding parasite gene expression during infection of the tick vector or mammalian host, which has limited the development of effective control strategies to alleviate the losses to the cattle industry. To understand Babesia gene regulation during tick and mammalian host infection, we performed high throughput RNA-sequencing using samples collected from calves and Rhipicephalus microplus ticks infected with B. bigemina. We evaluated gene expression between B. bigemina blood-stages and kinetes and compared them with previous B. bovis RNA-seq data. The results revealed similar patterns of gene regulation between these two tick-borne transovarially transmitted Babesia parasites. Like B. bovis, the transcription of several B. bigemina genes in kinetes exceeded a 1,000-fold change while a few of these genes had a >20,000-fold increase. To identify genes that may have important roles in B. bigemina and B. bovis transovarial transmission, we searched for genes upregulated in B. bigemina kinetes in the genomic datasets of B. bovis and non-transovarially transmitted parasites, Theileria spp. and Babesia microti. Using this approach, we identify genes that may be potential markers for transovarial transmission by B. bigemina and B. bovis. The findings presented herein demonstrate common Babesia genes linked to infection of the vector or mammalian host and may contribute to elucidating strategies used by the parasite to complete their life cycle.